High resolution human clustering based on complex signal correlation coefficients - Rudrappa, Manjunath Thindlu; Herschel, Reinhold (2021 18th European Radar Conference (EuRAD), 2022)
In this paper, we propose an algorithm to cluster human subjects based on complex signal correlation coefficients of detected voxels. The clustered positions obtained by the proposed algorithm were used to detect life signs and were matched with the images photographed at the time of the experiment with high accuracy.